2020
DOI: 10.3390/genes11040414
|View full text |Cite
|
Sign up to set email alerts
|

CircRNA Expression Profile during Yak Adipocyte Differentiation and Screen Potential circRNAs for Adipocyte Differentiation

Abstract: The yak (Bos grunniens) is subjected to nutritional deficiency during the whole winter grazing season; deciphering the adipose metabolism and energy homeostasis under cold and nutrients stress conditions could be a novel way to understand the specific mechanism of energy metabolism. Circular RNAs (circRNAs) have elucidated that they play a key role in many biological events, but the regulatory function of adipose development remains mostly unknown. Therefore, the expression pattern of circRNAs were identified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 65 publications
2
21
0
Order By: Relevance
“…Thus, a single circRNA can bind to a considerable number of miRNAs, and a miRNA can also target many circRNAs simultaneously. These results are consistent with previous studies in human visceral preadipocytes and adipocytes [ 7 ] and yak adipocytes [ 11 ]. This finding suggests that circRNAs, as miRNA sponges, have a complex regulatory relationship in abdominal fat tissue development or adipogenesis in chickens.…”
Section: Resultssupporting
confidence: 94%
See 1 more Smart Citation
“…Thus, a single circRNA can bind to a considerable number of miRNAs, and a miRNA can also target many circRNAs simultaneously. These results are consistent with previous studies in human visceral preadipocytes and adipocytes [ 7 ] and yak adipocytes [ 11 ]. This finding suggests that circRNAs, as miRNA sponges, have a complex regulatory relationship in abdominal fat tissue development or adipogenesis in chickens.…”
Section: Resultssupporting
confidence: 94%
“…In the Chinese Erhualian pig, Liu (2019) identified many DE circRNAs in adipose tissue of intramuscular, subcutaneous, peritoneal and mesenteric adipose tissues [ 8 ] and between subcutaneous preadipocytes and adipocytes [ 9 ]. In yaks ( Bos grunniens ), a previous study found 211 DE circRNAs from adipose tissue in yaks of two age groups [ 10 ], and another study identified 7,203 circRNAs and 136 DE circRNAs during yak adipocyte differentiation [ 11 ]. In addition, Huang (2019) identified 5,141 circRNAs and 252 DE circRNAs from the adipose tissue of adult and young Chinese buffaloes [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…A recently published report indicated that the expression of two circRNAs, 19:45387150|45389986 and 21:6969877|69753491, was strongly correlated with fat deposition associated genes in Chinese Buffalo (Bubalus bubalis) [75]. In the same context, Zhang et al identified six circRNAs, novel_circ_0009127, novel_circ_0000628, novel_circ_0011513, novel_circ_0010775, novel_circ_0006981, and novel_circ_0001494 that were related to Yac (Bos grunniens) adipogenesis [76]. In cattle adipocytes, circFUT10 was found to promote adipocyte proliferation and inhibit adipocyte differentiation via sponging let-7 binding of let-7c [77].…”
Section: Circrnas In Adipogenesis and Obesitymentioning
confidence: 99%
“…The analyses of circRNA conservation were conducted according to a previous study [42]. Mouse and human circRNA data were obtained from circBase (http://www.…”
Section: Circrna Conservation Analysis Among Human Mouse and Goatmentioning
confidence: 99%